Penurunan Kadar BOD, COD dan TSS pada Limbah Tahu Menggunakan Effective Microorganism-4 (EM4) Secara Aerob - Kartika Lingga Sari; Zulfikar Ali As; Hardiono Hardiono (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2017)
Abstract : Decreased Levels BOD, COD and TSS Waste Of Tahu Using Effective Microorganism-4 (EM4) In Aerobic. Wastewater was generated from industry tahu still contains levels of polluters such as BOD, COD and TSS are still high that can pollute waterways, Therefore it must be lowered levels before discharge into waterways. One way to do is wastewater treatment with EM4. This type of research was a quasi experiments aimed to determine the reduced levels of BOD, COD and TSS waste of tahu with wastewater treatment using the activator Effective Microorganism-4 (EM4) in aerobic with variation concentrations of 0%, 3%, 5%, 7% and retention time of 72 hours, 144 hours, 216 hours. The results showed the highest decrease levels wastewater concentration treatment of 7% EM4 with retention time of 216 hours with a BOD value 399,9 mg/L (88,8%), COD 1355,2 mg/L (85,3%) and TSS 287 mg/L (72,7%). Data analysis used two-way anova in the treatment group EM4 concentration and retention time obtained p value = 0.000 and α = 0.05 the results showed that there were significant differences due to variations in the concentration of EM4, due to the retention time and due to the effects of interactions EM4 concentration with retention time. The treatment results still exceeded the quality standard so before doing aerobic treatment, the first can do anaerobic treatment, so that wastewater treatment is getting better effluent. Keywords: Waste of tahu; levels of BOD; COD;TSS; EM4; retention time.